(untitled) (Research, Society and Development, 2023)
Cardiovascular diseases are liable for many deaths and hospitalization in Brazil and world, therefore, experimental studies with animal models are key to inducing dyslipidemias by food in order to discover causes and treatments. Diets formulated with a combination of purified and semi-purified ingredients solve limitations due to the high price. The aim of this survey was to develop a less expensive semi-purified high-fat diet for increased dyslipidemia in rats. So, 21 male rats (Rattus norvegicus, wistar) were randomly divided into three groups and fed even four weeks with Control Diet (CD), Hyperlipidic Diet Test (HDT) and Commercial Hypercholesterolemic Diet (HDC). The HDT was produced from CD, lard and eggs. During the experiment, feed intake, rat weight, plasma lipids and hepatic lipids were analyzed. The consumption of HDT and HDC diets was lower than CD, however, body mass gain was significantly higher for the two groups fed high-fat diets. Unlike HDC, HDT did not present a significant increase in visceral fat, liver weight or liver enzymes when compared to CD. It was observed that HLT showed a significant response to induce changes in plasma lipids, causing an increase in total cholesterol, LDL-c and triglycerides, leading to dyslipidemia, as did HLC, but with less deleterious effects on the liver and higher HDL-c values, indicating a relationship with the profile of fatty acids used in the rations.